ANALYSIS OF DISEASES DETECTED IN THE MEDICAL EXAMINATION IN THE CROSS SECTION OF THE YEAR IN SCHOOLS - Nodirbek Yusupov; Javokhir Khaitov (Western European Studies, 2025)
The preventive work carried out has created conditions for a sharp decrease in the incidence of certain diseases among students in 2022 and an increase in the effectiveness of their ability to work compared to 2021. Hygienic analysis of the disease condition in the cross section of years and hygienic analysis of the role and significance of the factors affecting it are explained by the condition of the disease and the corelial linkage of certain diseases.
Keywords: morbidity; preventive work; health